Pemeriksaan Multislice Computerized Tomography Sinus Paranasal dengan Klinis Tumor Sinonasal Menggunakan Kontras Injeksi Manual - Ananda, Afrilla Rika; Juliantara, I Putu Eka; Wijaya, Made (FORIKES, 2024)
Computed Tomography Scan is a very useful tool in assessing tumor size, nature, extent, and invasion. Multislice computerized tomography examination of the paranasal sinuses with clinical sinonasal tumors is performed using contrast to evaluate the condition of tumor growth. The purpose of this study was to determine the management and analyze the advantages and disadvantages of multislice computerized tomography examination of the paranasal sinuses with clinical sinonasal tumors. This study was a qualitative research with a case study approach. Researchers conducted observations and interviews with respondents. Furthermore, the data was analyzed and interpreted. The results of the study showed that from the initial observation, the patient registered at the radiology installation, and underwent urea and creatinine examinations. The examination began with informed consent. The protocol used was sinus contrast, the patient was positioned supine, the object was symmetrical, then pre- and post-contrast scanning was performed. Multi planar reconstruction was performed using a slice thickness of 2 mm axial, 4 mm coronal, and using 25 ml of contrast media through manual intravenous injection with a delay of 0 s. The advantage of this management is that the examination can still run when there is a problem with the injector so that the contrast can be injected manually. The disadvantage of this examination is that the scanning process depends on the speed of the nurse in injecting the contrast and the accuracy of the radiographer in scanning. It is concluded that multislice computerized tomography of the paranasal sinuses with clinical sinonasal tumors is practical and beneficial, but depends on the reliability of the nurse and radiographer.Keywords: multislice computerized tomography; paranasal sinuses; contrast ABSTRAK Computed Tomogrpahy Scan merupakan alat yang sangat berfungsi dalam penilaian ukuran tumor, sifat, luasnya, dan invasi. Pemeriksaan multislice computerized tomography sinus paranasal dengan klinis tumor sinonasal dilakukan menggunakan kontras untuk mengevaluasi kondisi pertumbuhan tumor. Tujuan penelitian ini yaitu untuk mengetahui tatalaksana dan menganalisis kelebihan dan kekurangan pemeriksaan multislice computerized tomography sinus paranasal dengan klinis tumor sinonasal. Studi ini merupakan riset kualitatif deskriptif dengan pendekatan studi kasus. Peneliti melakukan observasi dan wawancara terhadap responden. Selanjutnya data dianalisis dan diinterpretasikan. Hasil penelitian menunjukkan bahwa dari observasi awal, pasien melakukan mendaftar di instalasi radiologi, dan menjalani pemeriksaan ureum dan kreatinin. Pemeriksaan dimulai dengan informed consent. Protokol yang digunakan yaitu sinus kontras, pasien diposisikan supine, objek disimetriskan, lalu dilakukan scanning pra dan pasca kontras. Multi planar recontruction dilakukan menggunakan slice thickness axial 2 mm, coronal 4 mm, serta menggunakan media kontras 25 ml melalui injeksi intravena secara manual dengan delay 0 s. Kelebihan dari penatalaksanaan ini yaitu pemeriksaan tetap dapat berjalan ketika ada kendala pada injector sehingga kontras bisa dimasukkan melalui injeksi manual. Kekurangan dari pemeriksaan ini yaitu proses scanning bergantung pada kecepatan perawat dalam menyuntikkan kontras dan ketepatan radiografer dalam melakukan scanning. Disimpulkan bahwa multislice computerized tomography sinus paranasal dengan klinis tumor sinonasal praktis dan menguntungkan, namun tergantung kepada keandalan perawat dan radiografer.Kata kunci: multislice computerized tomography; sinus paranasal; kontras